Introducing Shariah compliant hotels as a new tourism product: the case of Malaysia - Mohd Fadil Mohd Yusof; Mohd Zulkifli Muhammad
This paper is concerned with the concept of Shariah compliant hotels which are introduced to attract a growing Muslim travelers market. Major attributes of Shariah compliant hotels are investigated based on the available literature and secondary data. The concept of Shariah compliant hotels should be clearly defined and it is suggested that the relevant stakeholders to play important roles in contributing to the understanding of such concept. The idea of setting up of Shariah compliant hotel is very interesting indeed considering the growing population of Muslim travelers. In the case of Malaysia, the concept of Shariah compliant hotel is yet to be explored and warranted further investigation. It is recommended that the setting up of Shariah compliant hotels to be promoted aggressively to stimulate the tourism industry which may be cater to the growing Islamic market especially from the Middle East region.